Pelatihan Penyusunan Modul Ajar Berbasis Augmented Reality Bermuatan Nilai Karakter Pancasila Untuk Guru Bahasa Indonesia Mts Se-Kota Cirebon - Veni Nurpadillah; Emah Khuzaemah; Inggit Nurul Istifaedah (Universitas Islam Negeri Siber Syekh Nurjati Cirebon, 2024)
TRAINING FOR PREPARING AUGMENTED REALITY-BASED TEACHING MODULES CONTAINING PANCASILA CHARACTER VALUES FOR MTS INDONESIAN LANGUAGE TEACHERS IN THE CITY OF CIREBON. Teaching modules and learning media are learning tools that must be prepared. One of the interactive learning media based on information and communication technology is Augmented Reality (AR). The use of augmented reality in learning that contains the Pancasila Character Values provides a more fun and interactive learning experience for students. In view of the problems of teachers who still experience difficulties in compiling teaching modules that suit students' needs, with the existence of PkM related to